Tingkat Problematika Administrasi Guru PAI pada Kurikulum Merdeka terhadap Kualitas Mengajar di Kelas Siswa SMK Al Mabrur Pejawaran Banjarnegara - Latifatun Nurohmah; Ngarifin Shidiq; Nur Farida (STIKes Ibnu Sina Ajibarang, 2025)
This study aims to examine the level of administrative problems experienced by Islamic Education (PAI) teachers in implementing the Merdeka Curriculum and its relationship to the quality of teaching in SMK Al Mabrur Pejawaran. The research is grounded in the concern that administrative burdens may affect teaching effectiveness. A descriptive quantitative method was used, with data collected through observation, interviews, questionnaires, and documentation. The sample consisted of 119 students and one PAI teacher. The results showed that the level of administrative problems was categorized as low, with an average score of 86.67%. Meanwhile, the teacher’s teaching quality was considered fairly good by students, with a mean score of 54.46. Statistical analysis using a one-sample t-test produced a significance value of 0.505, indicating no significant difference between the perceived teaching quality and the reference mean. This suggests that although the teacher faced administrative responsibilities, they did not directly hinder classroom performance. The implication is that well-managed administration can support the learning process. Systematic support and technical training are needed to help teachers balance their administrative and pedagogical roles effectively within the framework of the Merdeka Curriculum.